A new species of neoplecostomus eigenmann & eigenmann, 1888 (siluriformes: loricariidae: neoplecostominae) from the upper rio Parana basin - Andrade, Breno Neves [UNESP]; Langeani, Francisco [UNESP] (Soc Brasileira Ictiologia, 2014)
Neoplecostomus jaguari, a new neoplecostomine, is described based on material from the rio Jaguari, rio Tiete basin, southeastern Brazil. The new species differs from all congeners by having a conspicuous sexual dimorphism: females with 30-38 teeth in the dentary and 30-39 in the premaxilla, and males with 13-18 and 14-20 teeth, respectively (vs. number of teeth in the dentary and premaxilla approximately equivalent in all other species, except for N. langeanii in the premaxilla); females with larger mandibullary width, 18.5-21.6% HL, males 11.8-15.7% HL (vs. mandibullary width in males and females approximately equivalent); females with teeth longer and thin, males with teeth shorter and robust (vs. teeth similar in other species, except for N. langeanii in the premaxilla). Furthermore the new species is distinguished from all other species from the upper rio Parana basin by having a lateronasal plate either forming the border of the nostril or posteriorly displaced (vs. lateronasal plate absent). Finally, other useful character includes four to six plates between the frontal and prefrontal, herein called posteronasal plates (vs. one to three in all other species). An identification key to all Neoplecostomus species is provided.

Neoplecostomus jaguari, espécie nova de Neoplecostominae, é descrita com base em material do rio Jaguari, drenagem do rio Tietê, sudeste do Brasil. A espécie nova difere de todas as congêneres por apresentar dimorfismo sexual conspícuo: fêmeas com 30-38 dentes no dentário e 30-39 no pré-maxilar e machos com 13-18 e 14-20 dentes, respectivamente (vs. número de dentes no dentário e pré-maxilar aproximadamente equivalente em todas as outras espécies, exceto N. langeanii para o pré-maxilar); fêmeas com maior largura do mandibular, 18,5-21,6% CC, machos 11,8-15,7% CC (vs. largura do mandibular aproximadamente equivalente em machos e fêmeas); fêmeas com dentes longos e finos, machos com dentes curtos e robustos (vs. dentes similares nas outras espécies, exceto N. langeanii no pré-maxilar). Adicionalmente diferencia-se de todas as demais espécies da bacia do alto rio Paraná por apresentar a placa lateronasal formando a borda lateral da narina ou deslocada posteriormente (vs. placa lateronasal ausente). Finalmente, caracteres úteis para o reconhecimento da espécie nova incluem quatro a seis placas entre o frontal e pré-frontal, aqui denominadas placas posteronasais (vs. uma a três em todas as outras espécies). Uma chave de identificação para todas as espécies de Neoplecostomus é fornecida.
Keywords: Cascudos; Neoplecostomus paranensis; Neotropical region; Ostariophysi; Systematics